2010
DOI: 10.1016/j.joca.2010.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Association of radiographic and symptomatic knee osteoarthritis with health-related quality of life in a population-based cohort study in Japan: the ROAD study

Abstract: This cross-sectional study revealed that subjects with symptomatic knee OA had significantly lower physical QOL than subjects without it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
89
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 35 publications
3
89
0
4
Order By: Relevance
“…Although previous investigations have identified quality-of-life deficits in persons that are ACL deficient,27 after ACLR,17 28 29 and in those with symptomatic radiographic OA,30 to the best of our knowledge the relationship between MRI-defined OA and knee-related quality of life 3–10 years postinjury has not been previously reported. Our analyses suggest that when considered in linear combination MRI-defined OA, injury history, BMI, sex and time since injury explain 40.3% of the variability in KOOS quality-of-life score.…”
Section: Discussionmentioning
confidence: 80%
“…Although previous investigations have identified quality-of-life deficits in persons that are ACL deficient,27 after ACLR,17 28 29 and in those with symptomatic radiographic OA,30 to the best of our knowledge the relationship between MRI-defined OA and knee-related quality of life 3–10 years postinjury has not been previously reported. Our analyses suggest that when considered in linear combination MRI-defined OA, injury history, BMI, sex and time since injury explain 40.3% of the variability in KOOS quality-of-life score.…”
Section: Discussionmentioning
confidence: 80%
“…Third, comparisons with similar populations in other countries were not made due to the limited number of reports about the prevalence of nocturnal knee pain. Muraki et al suggested that there are differences in the characteristics of OA between Japan and other countries (33). Such investigations could supply further important information for the treatment and management of OA.…”
Section: Discussionmentioning
confidence: 92%
“…As a tool to evaluate HRQoL in the target population, medical outcome study short form-36, EuroQol-5 dimension (EQ-5D), and health utility index mark-3 are widely used [15]. Among these instruments, EQ-5D is a self-reported questionnaire that consists of five domains of HRQoL and one of standardized research tools developed in Europe to measure and describe HRQoL [16].…”
Section: Introductionmentioning
confidence: 99%